2017
DOI: 10.1152/ajpheart.00312.2017
|View full text |Cite
|
Sign up to set email alerts
|

Muscle sympathetic nerve activity and volume-regulating factors in healthy pregnant and nonpregnant women

Abstract: Healthy, normotensive human pregnancies are associated with striking increases in both plasma volume and vascular sympathetic nerve activity (SNA). In nonpregnant humans, volume-regulatory factors including plasma osmolality, vasopressin, and the renin-angiotensin-aldosterone system have important modulatory effects on control of sympathetic outflow. We hypothesized that pregnancy would be associated with changes in the relationships between SNA (measured as muscle SNA) and volume-regulating factors, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…Moreover, we found that they were strongly correlated with SNA. This is consistent with our recent work demonstrating a similar pattern in the third trimester of pregnancy (Charkoudian et al., ). Therefore, these findings suggest that during pregnancy, a complex mechanism underlying central sympathetic activation could be responsible for the observed increase in SNA.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, we found that they were strongly correlated with SNA. This is consistent with our recent work demonstrating a similar pattern in the third trimester of pregnancy (Charkoudian et al., ). Therefore, these findings suggest that during pregnancy, a complex mechanism underlying central sympathetic activation could be responsible for the observed increase in SNA.…”
Section: Discussionsupporting
confidence: 94%
“…As reported previously (Charkoudian et al . ; Jarvis et al . ), resting sympathetic burst frequency and burst incidence were higher in pregnant women compared to non‐pregnant women ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…All of the women included in the analysis had taken part previously in other studies in our laboratory (Charkoudian et al . ) and all provided their informed written consent at the time of assessment. All assessments were conducted in the morning.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSNA was recorded via peroneal microneurography as previously described (Charkoudian et al 2017). Briefly, the raw sympathetic signal was rectified and integrated to produce a neurogram with a characteristic bursting pattern.…”
Section: Muscle Sympathetic Nerve Activitymentioning
confidence: 99%